2014
DOI: 10.1007/s10571-014-0062-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of TRPVs, P2X3, and Parvalbumin in the Human Nodose Ganglion

Abstract: Immunohistochemistry for several neurochemical substances, the transient receptor potential cation channel subfamily V member 1 (TRPV1) and 2 (TRPV2), P2X3 receptor, and parvalbumin (PV), was performed on the nodose ganglion, pharynx, and epiglottis in human cadavers. The nodose ganglion was situated beneath the jugular foramen, and had a spindle shape with the long rostrocaudal axis. The pharyngeal branch (PB) issued from a rostral quarter of the nodose ganglion, whereas the superior laryngeal nerve (SLN) usu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…First, we only found P2X3 in a small population (18%) of IB4 fibers, thus it is possible that the afferent fibers containing P2X3 in our anatomical studies were not represented in the C-fiber populations studied in the prior electrophysiological studies. Previous studies have reported a similar proportion of nodose ganglion cells contain P2X3 in the rat (Wang et al , 2014), although much higher proportions have been reported in humans (Sato et al , 2014). The nodose ganglion is variably successful as a proxy for central terminals, since ion channels or receptors can be differentially trafficked to central and peripheral regions of the sensory neuron after synthesis in the ganglion.…”
Section: Discussionmentioning
confidence: 57%
“…First, we only found P2X3 in a small population (18%) of IB4 fibers, thus it is possible that the afferent fibers containing P2X3 in our anatomical studies were not represented in the C-fiber populations studied in the prior electrophysiological studies. Previous studies have reported a similar proportion of nodose ganglion cells contain P2X3 in the rat (Wang et al , 2014), although much higher proportions have been reported in humans (Sato et al , 2014). The nodose ganglion is variably successful as a proxy for central terminals, since ion channels or receptors can be differentially trafficked to central and peripheral regions of the sensory neuron after synthesis in the ganglion.…”
Section: Discussionmentioning
confidence: 57%
“…We have demonstrated expression of P2X3 and P2X2, and αβ-MeATP caused a [Ca 2+ ] i level increase in guinea pig nodose ganglion neurons, which is in agreement with previous studies. 23 , 39 αβ-MeATP was also able to depolarize guinea pig and human vagus nerves, and both the increase in calcium levels and the vagal depolarization evoked by αβ-MeATP were inhibited by the P2X1 and P2X3 inhibitor TNP-ATP and the P2X3 inhibitor AF-353. Both inhibitors were also shown to inhibit depolarization induced by TRPV4 ligands and hypo-osmotic solution in guinea pig and human vagus, confirming the hypothesis that TRPV4- and hypotonicity-mediated activation of vagal afferents is mediated by the release of ATP and activation of P2X3 receptors.…”
Section: Discussionmentioning
confidence: 97%
“…The superior cervical ganglion (SCG), a large sympathetic ganglion of the neck, is an interesting example of the complicated anatomical relationships between the parasympathetic and sympathetic nervous systems. The SCG is well known to be in close proximity of the nodose ganglion (NG) in most mammals including humans (Appelgren, Hansson, & Schmiterloew, 1963; Chungcharoen, De Burgh Daly, & Schweitzer, 1952; Fioretto, de Abreu, Castro, Guidi, & Ribeiro, 2007; Jamieson, Smith, & Anson, 1952; Phillips, Randall, & Armour, 1986; Randall, Armour, Randall, & Smith, 1971; Sato et al, 2014). Connections between the SCG and other cervical nerve systems are established by numerous small nerve branches and filaments arising from the NG, vagus nerve, and cervical plexus (Fioretto et al, 2007; Janes et al, 1986; Mitsuoka, Kikutani, & Sato, 2017; Nourinezhad, Mazaheri, & Biglari, 2015; Rodrigues, 1930).…”
Section: Introductionmentioning
confidence: 99%